Boundedness of Monge–Ampère singular integral operators on Besov spaces. Issue 11 (17th August 2020) - Han, Yongshen; Lee, Ming-Yi; Lin, Chin-Cheng
ABSTRACT: The purpose of this paper is to establish a theory of Besov spaces associated with sections under only the doubling condition on the measure and prove that Monge–Ampère singular integral operators are bounded on these spaces.